The effects of exercise based on adherence to ACSM recommendations on pulmonary function and quality of life in adults with asthma: a systematic review and meta-analysis - Li, Jinhan; Zhao, Jianxu; Wei, Jiahao; Wu, Baofa; Sun, Wuzhuang (Frontiers in Physiology, 2025)
BackgroundAdherence to ACSM exercise guidelines is linked to improved clinical outcomes in asthma patients, yet its effects on pulmonary function and QOL remain unclear. This study aims to comprehensively assess the impact of ACSM-based exercise adherence on lung function and patient-reported QOL in adults with asthma.MethodsA systematic search of Cochrane, Web of Science, Embase, and PubMed was conducted to review a meta-analysis on exercise regimens with tailored prescriptions for symptomatic bronchial asthma patients. Eligible randomized controlled trials comparing exercise interventions to non-intervention were selected and analyzed using SMD and 95% CI. Study quality was assessed using the revised Cochrane Risk of Bias tool, while Egger’s regression and Begg’s test evaluated publication bias. Studies were classified based on adherence to ACSM guidelines, and subgroup analyses employed a random-effects model where appropriate to enhance result reliability and interpretability.ResultsA total of 18 studies were included, with 9 classified as high adherence to ACSM guidelines and 9 as low/uncertain adherence. For FVC values were 0.72 (95% CI: 0.02, 1.42) and 0.64 (95% CI: 0.18, 1.11), respectively. The FEV1/FVC ratio was 0.19 (95% CI: −0.30, 0.69) versus 0.16 (95% CI: −0.95, 1.28). QOL scores demonstrated the most pronounced difference, with SMD at 0.85 (95% CI: 0.39, 1.32) for high adherence and 0.07 (95% CI: −0.22, 0.37) for low/uncertain adherence.ConclusionThis meta-analysis revealed that exercise interventions with high adherence to ACSM guidelines led to greater changes in QOL scores among asthma patients. While the high-adherence group outperformed the low/uncertain-adherence group in FEV1 and FVC, subgroup analysis failed to establish a significant difference. The modest impact on FEV1/FVC was likely influenced by substantial heterogeneity, potentially introducing bias in effect size estimation. Furthermore, the limited number of RCTs and small sample sizes may have undermined statistical power and result reliability.Systematic Review Registrationidentifier CRD42024553618.